Contribuição do engajamento dos gestores para o desempenho organizacional: um estudo nas Faculdades SENAC Santa Catarina na perspectiva da psicologia positiva - Bombazaro, Dian Carla Dias Isidoro (2020)
The theme of this Master's Thesis is engagement at work, which includes discussions about organizational performance and people management practices from the perspective of positive psychology. The general objective of this study was to evaluate the relationship between the level of engagement of managers at Senac/SC colleges and organizational performance. Specifically, it was necessary to describe the structure of Senac/SC's people management area, its policies, processes and practices; learn about the engagement practices adopted at each college, identifying those that make workers more engaged at work; measure the level of engagement of coordinators, using the Ultrecht Work engagement Scale (UWES); and, finally, verify and correlate organizational performance with the level of engagement of its managers. The study is justified by the belief that the results encourage managers of any organizations to debate more broadly about organizational performance, placing the person at its center. The originality is demonstrated based on the approach to work engagement that is still little explored in national literature, associated with the organization's behavior in terms of its performance. This is research developed at a descriptive level with a mixed data approach. The research subjects are the directors and core coordinators of the faculties. The process of data treatment, analysis and interpretation occurred in three distinct moments, the first referring to the systematic process of describing the content, followed by categorical analysis, and in the third moment multivariate statistics were used. The data described confirm the theoretical assumption that there is a positive relationship between the level of engagement of core directors and coordinators (higher education, administrative-financial, market relations) and the organizational performance of Senac/SC faculties. Likewise, the policies, processes and people management practices developed by DRH impact the engagement practices adopted by colleges. The limitations of the study include the survey research strategy applied in a Senac region in Brazil and the sample limited to colleges, so that the results cannot be generalized to the entire organization. The applicability is demonstrated in that the positive relationship between managers' engagement and organizational performance was evident. It is suggested that the Senac/SC Regional Board consider in its management model a set of indicators for measuring the positive state of its managers , represented by the dimensions vigor, dedication and absorption.